Magnolol Prevents Acute Alcoholic Liver Damage by Activating PI3K/Nrf2/PPARγ and Inhibiting NLRP3 Signaling Pathway - Liu, Xiao; Wang, Yanan; Wu, Di; Li, Shuangqiu; Wang, Chaoqun; Han, Zhen; Wang, Jingjing; Wang, Kai; Yang, Zhengtao; Wei, Zhengkai (Frontiers in Pharmacology, 2019)
Alcoholic liver damage (ALD) is a toxic liver damage caused by excessive drinking. Oxidative stress is one of the most crucial pathogenic factors leading to ALD. Magnolol is one of the main active constituents of traditional Chinese medicine Magnolia officinalis, which has been reported to possess many pharmacological effects including anti-inflammatory, anti-oxidantand anti-tumor. However, the effects of magnolol on ALD remain unclear. In this study, we firstly evaluated the protective effects of magnolol on ALD, and then tried to clarify the mechanism underlying the pharmacological activities. AST, ALT, GSH-Px and SOD were detected by respective kits. Histopathological changes of liver tissue were analyzed by H&E staining. The activities of PI3K, Nrf2 and NLRP3 signaling pathways activation were detected by western blotting analysis. It was showed that alcohol-induced the ALT and AST levels were significantly reduced by magnolol, but the antioxidant enzymes of GSH-Px and SOD levels were significantly increased. Magnolol attenuated alcohol-induced pathologic damage such as decreasing hepatic cord swelling, hepatocyte necrosis and inflammatory cell infiltration. Furthermore, it was found that magnolol inhibited oxidative stress through up-regulating the activities of HO-1, Nrf2, and PPARγ and the phosphorylation of PI3K and AKT. And magnolol also decreased inflammatory response by inhibiting the activation of NLRP3 inflammasome, caspase-1 and caspase-3 signaling pathway. Above results showed that magnolol could prevent alcoholic liver damage, and the underlying mechanism was through activating PI3K/Nrf2/PPARγ signaling pathways as well as inhibiting NLRP3 inflammasome, which also suggested magnolol might be used as a potential drug for ALD.